Problem Based Learning for Improving Students’ Cognitive Mastery in Science: Pembelajaran Berbasis Masalah untuk Meningkatkan Penguasaan Kognitif Siswa dalam Ilmu Pengetahuan Alam - Baidhowi, Muhammad; Efendi, Nur (Indonesian Journal of Education Methods Development, 2025)
Background: Cognitive learning outcomes in science remain low due to limited student engagement and the dominance of teacher-centered instruction. Specific Background: The human respiratory system is one of the IPA topics where students often struggle to master conceptual understanding. Gap: Previous studies widely examined PBL, but few focused specifically on its role in improving cognitive performance in this topic at the junior high school level. Aim: This study investigates how the PBL model enhances students’ cognitive learning outcomes. Methods: A quasi-experimental design with a pretest–posttest nonequivalent control group was conducted involving 50 eighth-grade students. Cognitive tests (20 items, C1–C5) were administered, and data were analyzed using normality, homogeneity, and independent sample t-tests. Results: The experimental class showed a higher improvement (44.4 to 72.6) compared to the control class (39 to 58.2), with a significance value of 0.04. Novelty: This study provides focused evidence of PBL effectiveness on respiratory system material. Implications: PBL can be applied to promote deeper conceptual understanding and student engagement in science learning. Highlights:• PBL strengthens cognitive mastery in science• Significant score improvement compared to conventional learning• Supports active inquiry and problem-solving practices Keywords: Problem Based Learning, Cognitive Outcomes, Science Learning, Respiratory System, Junior High School